RESPON ANGGREK MOKARA CHARK KWAN TERHADAP PERBEDAAN INTENSITAS CAHAYA (LIGHT INTENSITY RESPONSE OF ORCHID MOKARA CHARK KWAN) - A. D. Susanto; D. Widiyastoety; Y. Koesmaryono (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2006)
Orchid plant response to light intensity is dependent to crop variety. Generally, epyphyte orchid need less light intensity compare to teresterial orchid. The experiment aim to analyse the response of Mokara Chark Kwan to reducing light intensity. Randomised BlockDesign has been employed using five types of net with five replication. The main asumption to analyse is that plant well growing with sufficient nutrient and homogen age. The results indicated that more reducing light intensity is more increment of plant height and width of leave. Reducing light intensity, however, is not influence flower initiation and formation.